Assessment of quantitative traits of aggressiveness in Mycosphaerella graminicola on adult wheat plants. (12th March 2013) - Suffert, F.; Sache, I.; Lannou, C.
Abstract : Septoria tritici blotch, caused by Mycosphaerella graminicola, is a major foliar disease of wheat. The quantitative traits of pathogenicity are not comprehensively described in this pathosystem. The objective of this study was to identify and quantify the most relevant variables to describe traits of aggressiveness. Four wheat cultivars were inoculated in a greenhouse with four isolates. Inoculation was performed on a limited surface of the two uppermost leaves of adult plants. The dynamics of chlorotic, necrotic and sporulating areas were assessed twice a week. Pycnidia were counted at the same time. A Gompertz model was fitted to the resulting curves. Parameter combinations with easily interpreted biological relevance were examined further as descriptors of aggressiveness. Within each category of descriptor, those which were the most pairwise correlated and which explained the largest part of the variance were retained: incubation and latent period, development rate of sporulating area, maximal sporulating area, pycnidial density, and sporulation capacity. Correlations between these variables were discussed, assuming they reflect biological relationships between the corresponding aggressiveness quantitative traits. It is suggested that the selected variables, providing a good measure of M. graminicola fitness, can be used to estimate quantitative resistance of wheat to septoria tritici blotch, to characterize differences among isolates within a pathogen population, and to study quantitative adaptation of the pathogen to its host and to its environment.